The role of social identification, intergroup threat, and out-group derogation in explaining belief in conspiracy theory about terrorism in Indonesia - Mashuri, Ali (CONSORTIA ACADEMIA GROUP OF JOURNALS, PHILIPPINES, 2014)
This current research was to give new insight into group-based variables that frame belief in conspiracy about terrorism in Indonesia. Results (N= 201) showed that social identification with Moslem was positively related to out-group derogation to the Western people and to the belief that these people have conspired to instigate terrorism in Indonesia. We also demonstrated that, in line with prediction, the effect of social identification on out-group derogation and belief in conspiracy theory held only when participants perceived the Western people as highly threatening Islamic identity. This perceived intergroup threat also structured the mediation role of out-group derogation. More specifically, we hypothesized and found that out-group derogation mediated the effect of social identification on belief in the conspiracy theory, only when Moslem participants perceived the Western people as highly threatening their Islamic identity. We discussed these findings in terms of theoretical and practical implications